Religious Xenophobia In The Era Of Globalization And The Peculiarities Of Its Manifestation (Eurasian Journal of Humanities and Social Sciences, 2022)
This article analyzes the issues of manifestation of religious xenophobia in the era of globalization. In today's period, research within the framework of this topic plays an important role. The article mainly covers the main aspects and conclusions of the dissertation entitled "Religious xenophobia and features of its manifestation in the era of globalization" and serves to form a holistic picture in the reader on the topic. In particular, the article covers such issues as the relevance and necessity of the topic of the dissertation, the degree of study of the problem, the tasks of the study, the scientific novelty of the study, the practical result of the study, the scientific and practical significance of the research results and so on